1989
DOI: 10.1111/j.1365-2958.1989.tb00176.x
|View full text |Cite
|
Sign up to set email alerts
|

The major outer membrane protein of Chlamydia trachomatis: critical binding site and conformation determine the specificity of antibody binding to viable chlamydiae

Abstract: The major outer membrane protein (MOMP) is the prime candidate for the development of a chlamydial vaccine. Antibodies to the subspecies-specific epitope neutralize chlamydial infection. Monoclonal antibodies (MAbs) to this epitope were prepared either by immunization with whole chlamydiae or with a 16 amino acid synthetic peptide. The critical binding site on the subspecies epitope for these MAbs was determined to single amino acid resolution using several hundred solid-phase peptides. A frame shift of just o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…It was observed that the strength of this signal decreased with continued repeat cycling of the peptide-containing pins. A similar observation with certain peptides has been reported by Conlan et al (9).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…It was observed that the strength of this signal decreased with continued repeat cycling of the peptide-containing pins. A similar observation with certain peptides has been reported by Conlan et al (9).…”
Section: Resultssupporting
confidence: 90%
“…The DNA coding for the MOMP of C. trachomatis has been sequenced, and the antigenic determinants of the protein have been mapped with several monoclonal antibodies (MAbs) (1,6,8,9,31). This protein is composed of four variable domains (VDs), which are interspersed between conserved regions (30).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Epitopic domains within the variable segments of MOMP have been mapped to linear sequences of 9 to 11 amino acids using murine monoclonal antibodies and either free-solution peptides (Stephens et al, 1988) or expressing Agtl 1 recombinants (Baehr et al, 1988). Epitope localization and the structural requirements for antibody binding have been further defined to single amino acid resolution by solid-phase peptide mapping (Conlan et al, 1988(Conlan et al, , 1989. Typespecific epitopes have been demonstrated in both VSl for serovar A (Baehr et d., 1988) and VS2 for serovars B, C, L1 and L2 (Baehr etal., 1988;Conlan et al, 1988;Stephens et al, 1988) whilst subspecies-and species-specific epitopes were consistently found in VS4 (Baehr et al, 1988;Conlan et al, 1988 ;Stephens et al, 1988).…”
Section: J W C O N L a N A N D Othersmentioning
confidence: 99%
“…The critical binding sites of these antibodies were therefore investigated using the Geysen (1984) method of epitope mapping as we have previously described (Conlan et al, 1988(Conlan et al, ,1989. The results are presented in Fig.…”
Section: Epitope Mappingmentioning
confidence: 99%